Ossifying parosteal lipoma of the thoracic spine: a case report and review of literature - Zin W. Myint; Robert D. Chow; Lu Wang; Pauline M. Chou (Greater Baltimore Medical Center, 2015)
Introduction: Lipomas are derived from the mesodermal germ layer and are frequently encountered in adults, and account for almost 50% of all soft tissue tumors. Lipomas are classified based on their component tissues and location. A rare subtype, ossifying parosteal lipoma, accounts for 0.3% of all lipomas and occurs with intimate association with the underlying periosteum of the adjacent bone. Though lipomas are considered to be benign tumors, ossifying parosteal lipomas can manifest symptoms due to their location and relationship to nearby skeletal tissues. We herewith report the first known case of ossifying parosteal lipoma presenting in the region of the thoracic spine. Case presentation: An otherwise healthy adolescent boy presented with a 3-year history of a slowly enlarging painless thoracic mass. A general physical examination was normal, aside from a painless 10 cm mobile, hard mass along the posterior spine in the region of T4 through T6. Musculoskeletal and neurovascular examinations were normal. An ultrasound suggested a solid, cylindrically shaped mass with diffuse ossification. The mass was resected, and the pathology revealed ossifying parosteal lipoma without evidence of malignancy. Conclusion: Ossifying parosteal lipomas are rare, benign soft tissue tumors that should be added to the differential diagnosis of thoracic masses.